Jam: Jam’iyah Diba’iyah: Internalisasi Nilai-Nilai Pendidikan Karakter Remaja di Masjid Nurul Adha Darmo Kali Wonokromo Surabaya - Mustofa, Mustofa; Razi, Fahrur (Transformatif, 2024)
This article aims to analyze Jami'yah Dibai'yah activities at Nurul Adha Mosque on Darmo Rejo Street, Wonokromo, Surabaya, with a focuson the internalization of character education among the mosque's teenagers. Jami'yah Dibai'yah is a religious tradition that remains preserved, involving weekly recitations praising Prophet Muhammad PUBH. The article examines how these activities serve to instill values of character education in teenagers. The research method used is descriptive qualitative, with data collected through observations and interviews. The findings indicate that Jami'yah Dibai'yah functions as a tool for internalizing various character education values, including religiousness, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, love for the homeland, appreciation of achievements, friendliness and communication, love of peace, reading habits, environmental concern, social concern, and responsibility.